Is perinatal CoVID-19 possible: first results - M. A. Vashukova; V. A. Zinserling; N. Yu. Semenova; N. A. Lugovskaya; T. A. Narkevich; Yu. V. Sukhanova (Журнал инфектологии)
Among the problems associated with a new coronavirus infection, the possibility of its occurrence in pregnant women plays an important role. Until now, there is very little data on perinatal COVID-19, and there are no descriptions of structural changes in the afterbirth at all. Material and methods. A clinical and morphological analysis of 6 cases in which women with verified COVID-19 gave birth in an infectious hospital was performed. In all cases, the placenta was examined in detail morphologically using antibodies to the nucleoprotein and spike (S1 subunit spike protein) SARS-CoV-2. COVID-19 Results. It is shown that the clinical course of COVID-19 in pregnant women may be different, three were in the intensive care unit, including one was shown to be on a ventilator. 4 children were born at term, 2 children prematurely (at 31- 33 weeks of pregnancy). The condition of children in 5 nab. was assessed as satisfactory, only one child in serious condition was transferred to a children’s hospital. Intrauterine infection with the polymerase chain reaction documented in a single observation. When histological examination of the afterbirth in all observations, both in the maternal and fetal parts, changes characteristic of RNA viral infection was detected. Both of the studied antigens were found in moderate amounts in IHC. Conclusions. Intrauterine transplacental infection with a new coronavirus is certainly possible. Its frequency and clinical significance require further comprehensive study.